The Structure of the Hantavirus Zinc Finger Domain is Conserved and Represents the Only Natively Folded Region of the Gn Cytoplasmic Tail - Estrada, D. Fernando; Conner, Michael; St. Jeor, Stephen C.; De Guzman, Roberto N. (Frontiers in Microbiology, 2011)
Hantaviruses, of the family Bunyaviridae, are present throughout the world and cause a variety of infections ranging from the asymptomatic to mild and severe hemorrhagic fevers. Hantaviruses are enveloped anti-sense RNA viruses that contain three genomic segments that encode for a nucleocapsid protein, two membrane glycoproteins (Gn and Gc), and an RNA polymerase. Recently, the pathogenicity of Hantaviruses has been mapped to the carboxyl end of the 150 residue Gn cytoplasmic tail. The Gn tail has also been shown to play a role in binding the ribonucleoprotein (RNP), a step critical for virus assembly. In this study, we use NMR spectroscopy to compare the structure of a Gn tail zinc finger domain of both a pathogenic (Andes) and a nonpathogenic (Prospect Hill) Hantavirus. We demonstrate that despite a stark difference in the virulence of both of these viruses, the structure of the Gn core zinc finger domain is largely conserved in both strains. We also use NMR backbone relaxation studies to demonstrate that the regions of the Andes virus Gn tail immediately outside the zinc finger domain, sites known to bind the RNP, are disordered and flexible, thus intimating that the zinc finger domain is the only structured region of the Gn tail. These structural observations provide further insight into the role of the Gn tail during viral assembly as well as its role in pathogenesis.